The Wealthy, the Brilliant, the Few Elite Education in Contemporary American Discourse - Spieler, Sophie (American Culture Studies, 2021)
How does the US make sense of its elite educational system, given that it seems to be at odds with core American values, such as equality of opportunity or upward mobility? Sophie Spieler explores scholarly and journalistic investigations, self-representational texts, and fictional narratives revolving around the Ivy League and its peers in order to understand elite education and its peculiar position in American cultural discourse. Among the book's most surprising and groundbreaking insights is the tenacity and adaptability of meritocratic ideology across all three sub-discourses, despite its fundamental incompatibility with the American educational system.